Osteochondroma arising from a lumbar facet joint in a 16-year-old. Issue 3 (May 2015) - Hancock, Graeme E.; Mariathas, Chrishan; Fernandes, James A.; Breakwell, Lee M.; Cole, Ashley A.; Michael, Antony L.R.
Abstract : Osteochondromas are benign tumours of bony or cartilaginous origin, which may be solitary or multiple. They are rare in the axial skeleton and have previously been reported to arise from facet joints only in four cases in the English literature. We report the case of a 16-year-old girl who presented with a palpable bony lump and a short history of back pain. Imaging showed a bony lesion arising from a left-sided facet joint in the lumbar spine. Following excision biopsy, there was complete resolution of symptoms. The literature on the origin and management of spinal osteochondromas is discussed.